PEREKAMAN DATA SENSOR KE GOOGLE SHEETS MENGGUNAKAN SISTEM MIKROPENGENDALI ATMEGA16A DAN APLIKASI SERVER - Arief Hendra Saptadi; Achmad Solichan (PSRE UNIMUS, 2016)
There are various occasions where data taken from field measurements need to be stored remotely, but yet accessible from many places and by any means. The emergence of online data storage for documents such as Google Docs had made it possible to build a system that acquires data from sensors and stores them as an online document accessible anywhere. The purpose of this research is to develop a system prototype to store and display data from the result of measurements toGoogle Sheets through the use of ATmega16A microcontroller system and a server application. The proposed system consists of a data acquisition unit, a PC that acts as a server and web services. The data acquisition unit is made up from an ATmega16A microcontroller, LM35 astemperature sensor, photoresistor for light intensity measurement and FT232RL module for serial communication. Application server that runs on a PC is written in Processing programming language.The web services being used are Temboo and Google Sheets. From the test results it can be concluded that data acquisition unit had been able to transmit data to PC via serial communication, the server application was successfully built in terms of interface design and functionalities and a table in Google Sheets had been capable to store measurement results and display them correctly. In order to deliver a sense of real-time measurement, it is advisable to add a real-time clock chip module to microcontroller system such that the momentthe data arrive from sensors is recorded. The server application can be improved by the addition of local data logging feature to anticipate the loss of data caused by disturbances during onlinetransmission. Keywords: Data Logging, Sensors, Google Sheets, ATmega16A, Server Application